Theoretical substantiation of the methodology of technical and tactical training of qualified freestyle wrestlers - Norden, A.P.; Kozhanov, V.V.; Moskovsky, A.V. (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study is to theoretically substantiate the methodology of technical and tactical training of qualified freestyle wrestlers. Methods and structure of the study. To substantiate the methodology of technical and tactical training, a pedagogical experiment was conducted with the participation of freestyle wrestlers, the level of sports qualification - KMS, I category, light weight category. The pedagogical experiment was conducted on the basis of the Urmarskaya Secondary School named after A. F. Fedorov in the Urmarsky district of the Chuvash Republic. Results and conclusions. The technique was developed for wrestlers of the game style, combined fighting in order to increase the variability of the use of technical and tactical actions when exposed to disruptive factors in competitive activities. In this regard, the most important aspect of an athlete's technical fitness is the ability to combine various techniques into a rational chain of motor actions (technical and tactical complex), depending on the situation specific to a particular moment of competitive activity. A rationally constructed technical and tactical set of actions makes it possible to optimally link together consistently applied local offensive and defensive actions, which ensures the achievement of a given final result, taking into account the opponent's behavior. One of the indicators of the quality of technical and tactical training (hereinafter referred to as TTP) is their ability to master a combination style of fighting, successfully perform complex technical and tactical actions (hereinafter referred to as TTD) that require a certain amount of time for their tactical training, and are associated with the danger of losing in the opponent's retaliatory actions. Reducing the time an athlete spends on TTD preparation significantly affects the reliability of the bout result.